2015
DOI: 10.1007/s12541-015-0304-x
|View full text |Cite
|
Sign up to set email alerts
|

A methodology for optimizing modular design considering product end of life strategies

Abstract: Product modularity is a concept of clustering the independent components into logical units that are relatively independent to each other in functions. With the growing interest in environmental protection, the inclusion of product end of life issues during product design has been seen as a promising method to improve product utilization after its retirement. There are very few methodologies that deal with modularity at the conceptual design stage in which incorporate product end of life strategies and end of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
0
6
0
1
Order By: Relevance
“…Cheng et al 15 proposed a module division method of the heavy‐duty machine tool for green remanufacturing based on axiomatic design, and extended the process of remanufacturing to design domains, but did not consider the characteristics of various stages of the product life cycle. Sakundarini et al 12 identified the relationship between product end of life strategies and modular design from the aspects of functionality, structure, disassembly ability and materials. Ma and Kremer 1 developed a modular product design approach that used cost, environmental impact, and labor time as indicators of economic, environmental, and social sustainability dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Cheng et al 15 proposed a module division method of the heavy‐duty machine tool for green remanufacturing based on axiomatic design, and extended the process of remanufacturing to design domains, but did not consider the characteristics of various stages of the product life cycle. Sakundarini et al 12 identified the relationship between product end of life strategies and modular design from the aspects of functionality, structure, disassembly ability and materials. Ma and Kremer 1 developed a modular product design approach that used cost, environmental impact, and labor time as indicators of economic, environmental, and social sustainability dimensions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, Zuidwijk and Krikke 30 identified three EOL options: the remanufacturing on a component level, recycling after complete disassembling of the product, recycling after partial disassembling of the product, and the setting in discharge. Sakundarini et al 12 identified also three EOL options: component lifetime, material compatibility, and recyclability. Li et al 22 considered three environmentally conscious option: reuse, recycle, and disposal, Ijomah et al 4 presented three remanufacturing drivers: environmental concerns (the need to reduce waste), legislation (international agreement to reduce the environmental impact of products), and economics.…”
Section: Fuzzy Correlation Analysis Among Components For Remanufacturingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Rose et al (1998), product recovery can be enhanced by proper design planning. This is important because incorporating design strategies such as ease of disassembly and material selection during the early stages of product design and development provides different options for recovery once the product has reached its EOL (Sakundarini, Taha, Ghazilla, & Abdul-Rashid, 2015;Simic, 2016). Products should be designed for ease of disassembly in order to reduce the likelihood of the parts being damaged when the products are disassembled (Guide, 2000), as well as to reduce time and costs (Afrinaldi, Saman, & Shaharoun, 2010;Ghazilla, Taha, Yusoff, Abdul-Rashid, & Sakundarini, 2014;Go et al, 2012;Saman, 2008).…”
Section: Factors That Influence Product Recovery Effectivenessmentioning
confidence: 99%
“…Chiu et al (2016) desenvolveram um método de projeto para verificar a quantidade ideal de módulos de um produto para minimizar os impactos ambientais sem impactar no desempenho produtivo. Sakundarini et al (2015) formularam um método de otimização para auxiliar os projetistas na concepção de produtos com estratégias de fim de vida adequadas e reduzir o impacto ambiental durante a retirada do produto do mercado. Assim, com o constante aumento da preocupação com o impacto ambiental dos produtos, estratégias modulares tendem a oferecer mais benefícios neste aspecto para as empresas num futuro próximo.…”
unclassified